Highly Efficient CRISPR/Cas9-Mediated Homologous Recombination Promotes the Rapid Generation of Bacterial Artificial Chromosomes of Pseudorabies Virus - Guo, Jin-Chao; Tang, Yan-Dong; Zhao, Kuan; Wang, Tong-Yun; Liu, Ji-Ting; Gao, Jia-Cong; Chang, Xiao-Bo; Cui, Hong-Yu; Tian, Zhi-Jun; Cai, Xue-Hui; An, Tong-Qing (Frontiers in Microbiology, 2016)
Bacterial artificial chromosomes (BACs) are powerful tools for the manipulation of the large genomes of DNA viruses, such as herpesviruses. However, the methods currently used to construct the recombinant viruses, an important intermediate link in the generation of BACs, involve the laborious process of multiple plaque purifications. Moreover, some fastidious viruses may be lost or damaged during these processes, making it impossible to generate BACs from these large-genome DNA viruses. Here, we introduce the CRISPR/Cas9 as a site-specific gene knock-in instrument that promotes the homologs recombination of a linearized transfer vector and the Pseudorabies virus genome through double incisions. The efficiency of recombination is as high as 86%. To our knowledge, this is the highest efficiency ever reported for Pseudorabies virus recombination. We also demonstrate that the positions and distances of the CRISPR/Cas9 single guide RNAs from the homology arms correlate with the efficiency of homologous recombination. Our work show a simple and fast cloning method of BACs with large genome inserted by greatly enhancing the HR efficiencies through CRISPR/Cas9-mediated homology-directed repair mechanism, and this method could be of helpful for manipulating large DNA viruses, and will provide a successful model for insertion of large DNA fragments into other viruses.